2008
DOI: 10.1038/ejhg.2008.72
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide linkage scan for atypical nevi in p16-Leiden melanoma families

Abstract: In most Dutch melanoma families, a founder deletion in the melanoma susceptibility gene CDKN2A (which encodes p16) is present. This founder deletion (p16-Leiden) accounts for a significant proportion of the increased melanoma risk. However, it does not account for the Atypical Nevus (AN) phenotype that segregates in both p16-Leiden carriers and non-carriers. The AN-affected p16-Leiden family members are therefore a unique valuable resource for unraveling the genetic etiology of the AN phenotype, which is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
5
12
0
Order By: Relevance
“…Again, this is similar to findings in CDKN2A families 4041 The presence of clinically atypical nevi has been suggested to be a modifier of melanoma risk in CDKN2A mutation carriers,40 41 and we observed that among affected subjects, the median age at first melanoma diagnosis was 7.5 years lower in atypical nevi positive than in negative family members. On the other hand, the frequency of these nevi was similar in affected and unaffected CDK4 positive subjects (table 3).…”
Section: Discussionsupporting
confidence: 90%
“…Again, this is similar to findings in CDKN2A families 4041 The presence of clinically atypical nevi has been suggested to be a modifier of melanoma risk in CDKN2A mutation carriers,40 41 and we observed that among affected subjects, the median age at first melanoma diagnosis was 7.5 years lower in atypical nevi positive than in negative family members. On the other hand, the frequency of these nevi was similar in affected and unaffected CDK4 positive subjects (table 3).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the association appeared to be restricted to families with CDKN2A mutations. Our results are consistent with findings from a previous genome-wide linkage scan for DN in melanoma families segregating p16-Leiden mutations, in which the strongest linkage signal for DN was mapped to chromosome 7q21.3, a region containing CDK6 (de Snoo et al , 2008). Given that the association was only seen in CDKN2A mutation positive families, it is not surprising that we did not replicate the association in other datasets that mostly included subjects negative for CDKN2A mutations.…”
Section: Discussionsupporting
confidence: 92%
“…Although the presence of CAN was associated with both melanoma development and a positive CDKN2A mutation status, none of all 97 participants could fulfill the AMS phenotype criteria. This is in line with the recent Dutch study about p16-Leiden founder mutation, AMS and genomewide scan for AMS genes [24].…”
Section: Discussionsupporting
confidence: 87%
“…In all examined anatomical sites, total mean number of nevi was significantly higher for mutation carriers, in correlation with other studies [12,24] and supporting that CDKN2A might probably be a nevogenic gene. Nevertheless, mean and median total naevus count in mutation carriers and in the whole cohort were lower than in previously reported population-based Swedish data [18,20].…”
Section: Discussionsupporting
confidence: 85%